Gas Sensors - Bahadar Khan, Sher; Asiri, Abdullah M.; Akhtar, Kalsoom (IntechOpen, 2020)
This book focuses on the applications of nanomaterials in the fabrication of gas sensors. It covers recent developments of different materials used to design gas sensors, such as conducting polymers, semiconductors, as well as layered and nanosized materials. The widespread applications of various gas sensors for the detection of toxic gases are also discussed. The book provides a concise but thorough coverage of nanomaterials applications and utilization in gas sensors. In addition, it overviews recent developments in and the fabrication of gas sensors and their attributes for a broad audience, including beginners, graduate students, and specialists in both academic and industrial sectors.